Carbohydrates on the growth of Cattleya schilleriana Reichb.f. seedlings (Orchidaceae) - Galdiano Junior, Renato Fernandes [UNESP]; Mantovani, Cibele [UNESP]; Macedo Lemos, Eliana Gertrudes de [UNESP] (Univ Federal Santa Maria, 2018)
The aim of the present study was to evaluate the effects of carbohydrate supplementation on the propagation of the orchid Cattleya schilleriana. The 120-d-old seedlings were subcultured in fructose-, glucose-, or sucrose-supplemented (0, 15, 30, and 45g L-1) 1/2 MS culture medium (half-strength macronutrient concentrations), using a completely random design with four repetitions per treatment. After 120d of treatment, root number and length, leaf number and length, and fresh weight were evaluated, and seedling survival was evaluated after 75d of acclimatization in a greenhouse. The in vitro growth data were submitted to regression analysis, whereas the percentage survival data were analyzed using ANOVA and Tukey's test. Both in vitro growth and ex vitro survival were lowest when the plantlets were grown in the absence of a carbohydrate source and highest (> 90% survival) when supplemented with glucose. According to our findings, the addition of either glucose (30g L-1) or sucrose (30g L-1) is recommended for mass propagation of C. schilleriana.
Keywords: in vitro culture; native orchid; glucose; sucrose; acclimatization